PRODUCTIVITY OF TYPE IN THE DERIVATIONAL PARADIGM OF OLD ENGLISH STRONG VERBS - Laura Pesquera Fernández (Revista de Lingüística y Lenguas Aplicadas)
This article aims at assessing the productivity of type of the derivational paradigms of Old English strong verbs, with which it contributes to the field of study of Old English word-formation. As a general conclusion, this analysis supports Hinderling’s (1967) and Seebold´s (1970) claim that the strong verb has to be the starting point of any description of word-formation in the Germanic languages. Other conclusions of the analysis include: (i) lexical productivity in Old English is due to affixation more often than compounding, the number of prefixal derivatives being slightly higher than the one of suffixal derivatives; (ii) the evolution from stem-formation to word-formation is in progress in Old English and, as a result, the derivation from variable bases plays an active role in the derivational morphology of the language, which displays around 900 derivatives that alternate with the inflectional forms of the corresponding strong verb.